Pegaptanib sodium for macular edema due to retinal-vein occlusion among patients intolerant to intravitreal triamcinolone acetonide - Ellen N. Yu, MD; Pik Sha Chan, MD; Amadeo A.S. Veloso, MD; Harvey S. Uy, MD (Philippine Journal of Ophthalmology)
Objective: To report the efficacy and safety of intravitreal pegaptanib sodium (IVP) on macular edema (ME) due to branch retinal-vein occlusion (BRVO) among patients intolerant to intravitreal triamcinolone acetonide (IVTA).